Assessment of the adequacy of EN ISO 15927‐4 reference years for photovoltaic systems. (11th April 2015) - García, Ignacio; Torres, José Luis
Abstract: The long‐term performance prediction of photovoltaic systems requires representative meteorological data from a particular location. Among the numerous proposals in the field of solar energy, most of them include procedures oriented towards the generation of test reference years (TRYs). These synthetic years are composed of the concatenation of 12 actual months of the time series of meteorological measurements. Using TRYs to simulate the performance of different types of solar energy systems reduces the computational effort of the simulation and simplifies the analysis of the results. In this sense, the technical standard EN ISO 15927‐4 describes a procedure for constructing a reference year suitable for evaluation of the annual heating and cooling long‐term needs in buildings. In this work, the adequacy of the EN ISO 15927‐4 reference year for photovoltaic systems was studied. The electricity production obtained by simulation with this TRY was compared with that obtained by the Weather Year for Solar Systems. This latter reference year only uses the monthly thermal energy collected by the system as a selection parameter of typical months. This comparison was performed for seven locations in the USA considering two 5.6 kWp grid‐connected photovoltaic systems that only differ in the solar tracking system. The suitability of the EN ISO 15927‐4 reference year for the estimation of the electrical energy generated by a photovoltaic system has been proved, showing good results in the annual and daily predictions in most of the cases studied. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The long‐term performance prediction of photovoltaic systems requires representative meteorological data from a particular location. This paper analyses the representativeness of the test reference year (TRY) proposed by the technical standard EN ISO 15927‐4 for photovoltaic systems at seven locations in the USA. Although this TRY is aimed at evaluating thermal loads in buildings, its suitability for the estimation of the electrical energy generated by a photovoltaic system in the long term has been proved in this work.